Acute Response Moderate Intensity Treadmill Training On Decrease Malondialdehyde In Obesity Women - Anam, Septiana Choerul; Sulistiawati, Sulistiawati; Purwanto, Bambang (STRADA : Jurnal Ilmiah Kesehatan, 2020)
This study aims to analyze the acute response of moderate intensity treadmill exercise to a decrease in MDA levels in obese women. True experiment research method with the randomized control group design posttest-only design using 21 obese women and randomly divided into three groups, namely K1 (n = 7, control without intervention), K2 (n = 7, moderate intensity interval training) and K3 (n = 7, moderate intensity continuous training). The intervention was carried out at 7-10 a.m. Moderate interval training interventions were carried out for 45 minutes, whereas moderate intensity continuous exercises were carried out for 40 minutes. Blood samples were taken 10 minutes after the intervention. MDA levels were measured using the Thiobarbituric Acid Reactive substance (TBARs) method. The results were obtained at K1 (811,286 ±72,539) ng / mL, K2 (615,571 ± 96,855) ng / mL, K3 (658,429 ± 113,934) ng / mL and (p =0.003)